2019
DOI: 10.1177/0963689719885083
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 Promotes Human Lung Cancer Cell Apoptosis via Akt/Gsk3β Signaling Induced by Resveratrol

Abstract: Protein arginine methyltransferase 5 (PRMT5) is implicated in various types of human cancer and tumor development, especially in lung cancer. Nevertheless, it is still unclear whether suppression of PRMT5 could promote lung cancer cell apoptosis and chemosensitivity induced by resveratrol, and the underlying molecular mechanism remains completely unknown. Here, we showed that PRMT5 was overexpressed in human lung cancer tissues and different types of lung cancer cell lines. Moreover, we constructed PRMT5 stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…We regulated the expression of PRMT5 in BCCs, finding that silencing the expression of it could suppress the proliferation and invasion of BCCs and promote their apoptosis. A previous study revealed that PRMT5 was highly expressed in triple-negative BC, and it believed that PRMT5 was necessary for cell proliferation, 19 and some studies about other tumors also reported that PRMT5 had certain regulatory effects on proliferation, invasion and apoptosis of tumor cells, 20,21 which was consistent with our results. The abnormality of aerobic glycolysis is considered as one of the tumor markers, and in BC, aerobic glycolysis can not only provide nutrition for cell proliferation but also help to promote cell proliferation and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…We regulated the expression of PRMT5 in BCCs, finding that silencing the expression of it could suppress the proliferation and invasion of BCCs and promote their apoptosis. A previous study revealed that PRMT5 was highly expressed in triple-negative BC, and it believed that PRMT5 was necessary for cell proliferation, 19 and some studies about other tumors also reported that PRMT5 had certain regulatory effects on proliferation, invasion and apoptosis of tumor cells, 20,21 which was consistent with our results. The abnormality of aerobic glycolysis is considered as one of the tumor markers, and in BC, aerobic glycolysis can not only provide nutrition for cell proliferation but also help to promote cell proliferation and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…As is known, AKT substrate GSK3β is negatively modulated by AKT activity, while activated GSK3β-Ser9 (non-phosphorylated state) is reported to regulate cell cycle analysis and apoptosis [38][39][40]. In our research, we also analyzed the effects of LF-MF on the activities of GSK3β in MCF-7 and ZR-75-1 cells.…”
Section: Discussionmentioning
confidence: 89%
“…It has been known that resveratrol can increase the sensitivity of tumor cells to other drugs besides its anticancer effects 43 , 44 . Resveratrol is also able to reverse the drug resistance of cancer cells 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that resveratrol effectively inhibited in vitro growth of ATC cells [19][20][21][22], and has preventive and therapeutic effect on the thyroid carcinogenesis induced by diethylnitrosamine (DEN), N-methyl-Nnitrosourea (MNU) and dihydroxydipropylnitrosamine (DHPN) [41]. Although resveratrol is able to enhance chemosensitivity of the cultured cancer cells [43,44], the impacts of resveratrol on docetaxel/ doxorubicin-resistant ATC cells remain unknown. It would be therefore of clinical significance if the anti-ATC effects and the conversion ability of resveratrol to docetaxel/doxorubicin-resistance can be confirmed in vivo.…”
Section: Discussionmentioning
confidence: 99%